Communication Strategies for Level 1 Indonesian Language for Foreign Speakers: Case Study of the Indonesian Embassy in Vientiane, Laos: - Septiani, Wita (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
One type of Indonesian language learning program is Indonesian for Foreign Speakers (BIPA). As the name suggests, this Indonesian language learning program is specifically for foreigners. The objectives of BIPA learning include not only linguistic aspects but also an introduction to Indonesian culture. The purpose of this study is to describe the communication strategies used by BIPA Level 1 learners at the Indonesian Embassy (KBRI) in Vientiane, Laos. This study employs a descriptive qualitative method, utilising a case study to present findings related to the research objectives. This study took place from April to November 2021. Data on communication strategies include the verbal and nonverbal behaviour of BIPA Level 1 learners at the Indonesian Embassy in Vientiane, Laos. The research data consist of the communication strategies employed by BIPA Level 1 learners at the Indonesian Embassy in Vientiane, Laos. The data sources were BIPA learners and teachers at the Indonesian Embassy in Vientiane, Laos. The research data were collected using a non-test instrument, namely an interview guide. The interview guide was structured objectively and systematically to ensure content validity. Data collection used the Zoom application. Data on the communication strategies of BIPA Level 1 learners at the Indonesian Embassy in Vientiane, Laos, were analysed using a qualitative approach. The results of this study indicate that the communication strategies employed by BIPA Level 1 learners include translation, paraphrasing, and reduction strategies.